Gender Dysphoria and Mental Health - M. Barbosa Pinto; F. Tavares; M. Viseu (European Psychiatry, 2022)
Introduction Gender dysphoria is characterized by a mismatch between the biological sex and gender identity of a person, frequently associated to distress or discomfort. Many transgender people will seek professional help to obtain a congruence between the gender identity and the body.